Preservative effect of Asparagus racemosus: A novel additive for bioactive edible films for improved lipid oxidative stability and storage quality of meat products. (May 2018) - Noor, Sabahu; Bhat, Z.F.; Kumar, Sunil; Mudiyanselage, Reshan J.
Abstract: Asparagus racemosus was used as a bioactive ingredient for the development of a novel calcium alginate edible film with preservative potential for improved lipid oxidative stability and storage quality of meat products. Chevon sausages were used as a model system and were aerobically packaged in the edible films incorporated with A. racemosus viz. T0 (0.0%), T1 (1.0%) and T2 (2.0%) and were stored under refrigerated (4 ± 1 °C) conditions. Products packaged in T1 and T2 edible films exhibited significantly ( P  < 0.05) lower values for TBARS (mg malonaldehyde/kg), microbial counts (cfu/g) and FFA (% oleic acid) indicating the bioactive properties of the developed films. Significantly ( P  < 0.05) higher sensory scores were recorded for the products packaged in T1 and T2 films. A. racemosus added antioxidant and antimicrobial properties to the developed films which improved the lipid oxidative stability and storage quality of the model meat product. Highlights: A novel calcium alginate edible film incorporated with Asparagus racemosus was developed. Developed films had significant antimicrobial and antioxidant properties. A significant improvement was observed in the lipid oxidative stability. The developed films improved the microbial and sensory quality of the model meat product.